International immunities for the diplomatic envoy in Islamic law and international agreements - Alghamdi, Ali Faraj (Journal of Economic, Administrative and Legal Sciences, 2021)
The Diplomatic Agent has great significance at the present time because of the protection and care of the interests of individuals and states have been provided by him. The diplomacy has become the basis for preparing the foreign policy of states, as through diplomatic relations states solve many problems of peace and war and other interests of states. For that many International Conventions and Agreements were concluded to regulate diplomatic relations and lay down the rules for diplomatic protection and immunities. The most important of these international Conventions is the Vienna Convention for Diplomatic Relations 1961. Which brought special privileges and immunities for Diplomatic Agents Due to the significance of the matter, the researcher attempted through the study to shed light on “International Immunities Diplomatic Envoys in International Agreements and Islamic Sharia” by discussing the concept of Diplomatic Envoys, their duties, and the international immunity in International Law and Islamic Sharia. Through highlighting the types of immunities and their scope in International Law and Islamic Sharia, it appears that the Islamic Sharia was long ahead before nations in enforcing immunities rules and international protection of Diplomatic Agents. Thus, it has been the best influence in the international direction to implement rules of diplomatic representation, making it international law. In my study, I followed the inductive analytical approach which is approach through which the texts mentioned in the international laws that regulate the international immunity of the diplomatic envoy are extrapolated and analyzed. The conclusion included the results and recommendations of the research.